PENGGUNAAN LAYANAN JASA TRANSFER MELALUI MUAMALAT DIN (DIGITAL ISLAMIC NETWORK) DALAM MENINGKATKAN LOYALITAS NASABAH - Sudianto Sudianto; Linda Linda (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2023)
Transfers at Muamalat Bank can be done without going to the bank directly, namely making transfers via Muamalat DIN. Muamalat DIN is a mobile banking application by Bank Muamalat which can be accessed by its customers. At Muamalat DIN there is a transfer service which allows users to make transfers via Muamalat DIN. The aim of this research is to determine the use of transfer services via Muamalat DIN (Digital Islamic Network) in increasing customer loyalty at Bank Muamalat KCP Sumenep. To find out customer problems using transfer services via Muamalat DIN (Digital Islamic Network) at Bank Muamalat KCP Sumenep. To find out more about the use of transfer services through Muamalat DIN in increasing customer loyalty, researchers used a qualitative field research approach. The methods used are interviews, observation, documentation. The results of this research show that using transfer services via Muamalat DIN can increase customer loyalty because customers do not need to come to the bank to make a transfer, just use the Muamalat DIN application. The obstacles faced by customers using transfer services via Muamalat DIN are that some customers experience network problems, system repairs at the bank and human error or customer errors in making transfers and blocking of the Muamalat DIN application due to errors in entering the TIN code.